THE INFLUENCE OF FINANCIAL KNOWLEDGE AND FINANCIAL ATTITUDES ON THE FINANCIAL MANAGEMENT BEHAVIOR OF WEAVER UMKM PEOPLE IN BENGKALIS VALUE FROM A SHARIA ECONOMIC PERSPECTIVE - Rizuan, Syahrul; Aji Purwanto, Muhamad; Saifullah (Program Studi Manajemen Keuangan Syariah, 2025)
This research is motivated by the rapid development of the Micro, Small and Medium Enterprises (UMKM) sector in Indonesia, which is supported by government policies as stated in Law Number 20 of 2008. Even though UMKM contribute significantly to the economy, there are still challenges in financial management. faced by business actors, especially in weaving craft centers in Bengkalis. This research aims to analyze the influence of financial knowledge and financial attitudes on financial management behavior among weaving UMKM in Bengkalis from a sharia economic perspective. The method used is a quantitative descriptive study with primary data collection through closed questionnaires which are analyzed using statistical techniques. The research results show that financial knowledge and financial attitudes have a positive and significant influence on the financial management behavior of weaving craftsmen. Financial knowledge shows tcount 6.827 (significance 0.000), financial attitude tcount 2.636 (significance 0.011), and the combination of both F count 37.356 (significance 0.000). The R Square value of 0.624 shows that 62.4% of financial management behavior is influenced by financial knowledge and attitudes, the remaining 37.6% by other factors. The sharia economic perspective also emphasizes the importance of transparent and accountable financial management, so that UMKM can contribute more optimally to economic development